Organization of management and structure in local networks internet of things - U. A. Vishniakou; A. H. Al-Masri; S. K. Al-Haji (Системный анализ и прикладная информатика, 2020)
Internet of Things (IoT) symbolic formula is given. The analysis of management technologies both in the network structures of infocommunications, based on the NSMP, and on local networks of the Io T. Two approaches for implementing the management process in infocommunication networks are shown: one is based on creating special software tools, the second is based on the working with data describing the network device. The basic operations of SNMP are given. Four levels of IoT in local network structure are described: smart sensors, network vehicles, services, and applications. Structure of local network of IoT which includes smart sensors, transport environment, services and applications information representation in network use semantic web are considered.The structure of multi-agent system (MAS) of milk farms analyzing in Leban (MASMFA) for monitoring of production quality. MASMFA structure has many agents such as quality milk sensors, agents of communications, data base, analysis of the information received from sensor agents, decision-making. This system implements the functions to ensure the required class of milk quality and based on IoT local network construction. The information algorithm processing in such IoT is proposed. Milk sensor shell be periodically queried, their values will be recorded in the server database. The decisionmaking subsystem will issue data on milk quality to the farm administrator on a mobile device. The server structure will be implemented using a cloud service. Implementation this Internet of things network is being developed using LTE technology.